Assessment of knowledge and awareness of safe disposal of unused or expired medication in Saudi Arabia: A cross-sectional study - Abdulhamid Althagafi; Mohannad Alshibani; Samah Alshehri; Ahmed Noor; Alaa Baglagel; Tahani Almeleebia (Elsevier, 2022)
Background: Poor waste management of unused or expired medications jeopardizes healthcare staff, employees who oversee medical waste, patients and their families, the neighboring population, and environmental contamination. In addition, the inappropriate treatment or disposal of that waste leads to. In addition, medical waste disposal exerts an intolerable burden on the economy of health care facilities. Currently, there is a lack of data in community settings regarding adequate methods of medication disposal in Saudi Arabia. Aim of the Study: The current study aimed to evaluate current knowledge and awareness of the safe disposal of unused or expired medicines in the Saudi Arabia. Method: A survey study was conducted in Saudi Arabia within 5 months from October 2021-February 2022. The survey was distributed to participants via social media channels. The questionnaire was constituted of 16 items divided into three sections: demographic information, quantification, and characterization of unused and expired medication at home, and practice and attitude regarding the disposal of unused or expired medication. Results: The survey was taken by 1105 participants and 1100 (99.54%) participants completed the survey. The study found that (49.1%) of participants stored medicines at home and these medicines were mainly stored in the refrigerator (64.4%). Household trash was the most frequent method of disposal (79.5%). Non-prescribed medicines (67%) were mainly stored as unused or expiry medicines at home followed by prescribed medicines (51.9%). The main reason for the storage of unused/expired medicines at home was stopped medication after recovery (68.5%). Only 8.4% of participants had received appropriate education or training related to the correct disposal of medication. The best-practiced method to increase community awareness regarding the disposal of unused or expiry medicine was awareness through social networking (70.3%). In conclusion, patients' education regarding safe medication disposal and availability of medication disposal program is necessary to improve appropriate medication waste methods and decrease possible environmental harm.